Cataract surgery and primary intraocular lens implantation in children ⩽2 years old in the UK and Ireland: finding of national surveys. Issue 11 (16th June 2009) - Solebo, A L; Russell-Eggitt, I; Nischal, K K; Moore, A T; Cumberland, P; Rahi, J S
Abstract : Background: Current patterns of practice relating to primary intraocular lens (IOL) implantation in children ⩽2 years old in the UK and Ireland are investigated. Methods: National postal questionnaire surveys of consultant ophthalmologists in the UK and Ireland. Results: 76% of 928 surveyed ophthalmologists replied. 47 (7%) of the respondents operated on children aged ⩽2 with cataract. 41 (87%) of respondents performed primary IOL implantation, but 25% would not implant an IOL in a child under 1 year old. 88% of surgeons used limbal wounds, 80% manual capsulotomies, 98% posterior capsulotomies and 100% hydrophobic acrylic lenses. The SRK/T formula was most commonly used (70%). Exclusion criteria for primary IOL implantation varied considerably and included microphthalmos (64% of respondents), anterior and posterior segment anomalies (53%, 58%), and glaucoma (19%). Discussion: Primary IOL implantation in children ⩽2 has been widely adopted in the UK and Ireland. There is concordance of practice with regards to surgical technique and choice of IOL model. However, there is some variation in eligibility criteria for primary IOLs: this may reflect a lack of consensus on which children are most likely to benefit. Thus, there is a need for systematic studies of the outcomes of primary IOL implantation in younger children.